Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Temperature‐dependent growth and activity in a globally distributed nitrogen‐fixing haptophyte - Esther Wing Kwan Mak; Kendra A. Turk‐Kubo; Anna V. Voznyuk; Mary R. Gradoville; Tyler Coale; Kyoko Hagino; Jonathan P. Zehr (Limnology and Oceanography, 2025)
Dinitrogen (N 2 )‐fixing microorganisms play a crucial role in supplying nitrogen (N) to the oceans by converting atmospheric N 2 into bioavailable N. N 2 fixation was thought to be limited to warm oligotrophic ocean waters, but the association between the N 2 ‐fixing UCYN‐A cyanobacterium and specific haptophytes, including Braarudosphaera bigelowii and relatives, has been found in diverse ocean environments, including warm subtropical gyres, temperate coastal systems, and cold polar waters. UCYN‐A2, previously known as the symbiont of B. bigelowii , and now considered an early‐stage organelle that exchanges fixed nitrogen for fixed carbon, has only recently been cultured. This study investigated the growth and activity of B. bigelowii in response to a range of temperatures to better understand its global distribution and ecology. Incubation experiments were conducted with B. bigelowii to determine growth rates, carbon (C) and N 2 fixation rates, and cell sizes across a temperature range of 6–26°C. Growth rates were highest between 10°C and 22°C and lowest at 6°C and 26°C. Significant positive correlations were found between cell count‐based growth rates, C‐specific and N‐specific growth rates. Braarudosphaera bigelowii cell size increased at low temperatures. The growth and metabolic activity detected across a wide range of temperatures help to explain the wide geographic distribution of B. bigelowii . This study presents the first growth and activity measurements under a range of temperatures from B. bigelowii , providing vital information needed to understand the unique ecology of this organism and to parameterize its activity in ecosystem models.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A practical device to produce consistent, controlled cryoinjury on the skin - Emilee Herringshaw; Cemre Turk; Sandeep Korupolu; Moriel Tagar Sar-el; R. Rox Anderson; Yakir Levin; Joshua Tam (Cryobiology, 2024)

Composition and distribution of diazotrophs in the Baltic Sea - Ellen R. Salamon Slater; Kendra A. Turk-Kubo; Søren Hallstrøm; Katharina Kesy; Peeter Laas; Jonathan Magasin; Jonathan P. Zehr; Matthias Labrenz; Lasse Riemann (Estuarine, Coastal and Shelf Science, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Seasonal and spatial patterns in diazotroph community composition at Station ALOHA - Kendra A. Turk-Kubo; Britt A. Henke; Mary R. Gradoville; Jonathan D. Magasin; Matthew J. Church; Jonathan P. Zehr (Frontiers in Marine Science, 2023)
Dinitrogen (N 2 ) fixation is carried out by specialized microbes, called diazotrophs, and is a major source of nitrogen supporting primary production in oligotrophic oceans. One of the best-characterized diazotroph habitats is the North Pacific Subtropical Gyre (NPSG), where warm, chronically N-limited surface waters promote year-round N 2 fixation. At Station ALOHA (A Long-Term Oligotrophic Habitat Assessment) in the NPSG, N 2 fixation is typically ascribed to conspicuous, filamentous cyanobacterial diazotrophs ( Trichodesmium and Richelia ), unicellular free-living Crocosphaera , and the UCYN-A/haptophyte symbiosis, based on using microscopy and quantitative PCR (qPCR). However, the diazotroph community in this ecosystem is diverse and includes non-cyanobacterial diazotrophs (NCDs). We investigated the diversity, depth distributions, and seasonality of diazotroph communities at Stn. ALOHA using high throughput sequencing (HTS) of nifH gene fragments from samples collected throughout the euphotic zone (0-175 m) at near-monthly intervals from June 2013 to July 2016. The UCYN-A symbioses and Trichodesmium sp. consistently had the highest relative abundances and seasonal patterns that corroborated qPCR-based analyses. Other prevalent community members included a new Crocosphaera -like species, and several NCDs affiliated with γ- and δ-proteobacteria. Notably, some of the NCDs appear to be stable components of the community at Stn. ALOHA, having also been reported in prior studies. Depth and temporal patterns in microdiversity within two major diazotroph groups ( Trichodesmium and UCYN-A) suggested that sub-populations are adapted to time- and depth-dependent environmental variation. A network analysis of the upper euphotic (0-75 m) HTS data identified two modules that reflect a diazotroph community structure with seasonal turnover between UCYN-A/Gamma A, and Trichodesmium/Crocosphaera . It also reveals the seasonality of several important cyanobacteria and NCDs about which little is known, including a putative δ-proteobacterial phylotype originally discovered at Stn. ALOHA. Collectively, these results underscore the importance of coupling nifH gene HTS with other molecular techniques to obtain a comprehensive view of diazotroph community composition in the marine environment and reveal several understudied diazotroph groups that may contribute to N 2 fixation in the NPSG.

Sex-specific developmental trajectories in an extremely sexually size dimorphic spider - Janko Šet; Eva Turk; Rok Golobinek; Tjaša Lokovšek; Matjaž Gregorič; Shakira Guaní Quiñones Lebrón; Matjaž Kuntner; Charles R. Haddad; Klemen Čandek; Simona Kralj-Fišer (The Science of Nature, 2021)

Light and depth dependency of nitrogen fixation by the non‐photosynthetic, symbiotic cyanobacterium UCYN‐A - Mary R. Gradoville; Ana M. Cabello; Samuel T. Wilson; Kendra A. Turk‐Kubo; David M. Karl; Jonathan P. Zehr (Environmental Microbiology, 2021)
Summary The symbiotic cyanobacterium UCYN‐A is one of the most globally abundant marine dinitrogen (N 2 )‐fixers, but cultures have not been available and its biology and ecology are poorly understood. We used cultivation‐independent approaches to investigate how UCYN‐A single‐cell N 2 fixation rates (NFRs) and nifH gene expression vary as a function of depth and photoperiod. Twelve‐hour day/night incubations showed that UCYN‐A only fixed N 2 during the day. Experiments conducted using in situ arrays showed a light‐dependence of NFRs by the UCYN‐A symbiosis, with the highest rates in surface waters (5–45 m) and lower rates at depth (≥ 75 m). Analysis of NFRs versus in situ light intensity yielded a light saturation parameter ( I k ) for UCYN‐A of 44 μmol quanta m −2 s −1 . This is low compared with other marine diazotrophs, suggesting an ecological advantage for the UCYN‐A symbiosis under low‐light conditions. In contrast to cell‐specific NFRs, nifH gene‐specific expression levels did not vary with depth, indicating that light regulates N 2 fixation by UCYN‐A through processes other than transcription, likely including host–symbiont interactions. These results offer new insights into the physiology of the UCYN‐A symbiosis in the subtropical North Pacific Ocean and provide clues to the environmental drivers of its global distributions.

Latitudinal constraints on the abundance and activity of the cyanobacterium UCYN‐A and other marine diazotrophs in the North Pacific - Mary R. Gradoville; Hanna Farnelid; Angelicque E. White; Kendra A. Turk‐Kubo; Brittany Stewart; François Ribalet; Sara Ferrón; Paulina Pinedo‐Gonzalez; E. Virginia Armbrust; David M. Karl; Seth John; Jonathan P. Zehr (Limnology and Oceanography, 2020)
The number of marine environments known to harbor dinitrogen (N 2 )‐fixing (diazotrophic) microorganisms is increasing, prompting a reassessment of the biogeography of marine diazotrophs and N 2 fixation rates (NFRs). Here, we investigate the diversity, abundance, and activity of diazotrophic microorganisms in the North Pacific Subtropical Gyre (NPSG), a diazotrophic habitat, and the North Pacific Transition Zone (NPTZ), a region characterized by strong physical, chemical, and biological gradients. Samples were collected on two springtime meridional cruises during 2016 and 2017, spanning from 23.5°N to 41.4°N along 158°W. We observed an abrupt decrease in diazotrophic abundances near the southern edge of the NPTZ, which coincided with a salinity front and with a ∼10‐fold increase in Synechococcus abundance, but without a concomitant change in phosphate or nitrate concentrations. In NPSG waters south of this diazotrophic boundary, nifH genes and NFRs were consistently detected and diazotrophic communities were dominated by UCYN‐A, an uncultivated, symbiotic cyanobacterium (2.8 × 10 3 to 1.0 × 10 6 nifH gene copies L −1 ). There was a significant positive relationship between quantitative polymerase chain reaction‐derived UCYN‐A nifH gene abundances and community NFRs in the NPSG, suggesting a large contribution of UCYN‐A to community NFRs. In the NPTZ waters to the north, NFRs were low or undetected and nifH genes were rare, with the few detected sequences represented by UCYN‐A and noncyanobacterial diazotrophs. The patterns we observed in UCYN‐A abundance in the context of local biogeochemistry suggest that the environmental controls of this organism may differ from those of cultivated marine cyanobacterial diazotrophs.

Attenuation of lead toxicity by promotion of tolerance mechanism in wheat roots by lipoic acid - H. Turk; S. Erdal; U. Karayel; R. Dumlupinar (Cereal Research Communications, 2018)

Distinct Siderophores Contribute to Iron Cycling in the Mesopelagic at Station ALOHA - Randelle M. Bundy; Rene M. Boiteau; Craig McLean; Kendra A. Turk-Kubo; Matt R. McIlvin; Mak A. Saito; Benjamin A. S. Van Mooy; Daniel J. Repeta (Frontiers in Marine Science, 2018)

Differential effects of nitrate, ammonium, and urea as N sources for microbial communities in the North Pacific Ocean - I. N. Shilova; M. M. Mills; J. C. Robidart; K. A. Turk‐Kubo; K. M. Björkman; Z. Kolber; I. Rapp; G. L. van Dijken; M. J. Church; K. R. Arrigo; E. P. Achterberg; J. P. Zehr (Limnology and Oceanography, 2017)
Nitrogen (N) is the major limiting nutrient for phytoplankton growth and productivity in large parts of the world's oceans. Differential preferences for specific N substrates may be important in controlling phytoplankton community composition. To date, there is limited information on how specific N substrates influence the composition of naturally occurring microbial communities. We investigated the effect of nitrate ( ), ammonium ( ), and urea on microbial and phytoplankton community composition (cell abundances and 16S rRNA gene profiling) and functioning (photosynthetic activity, carbon fixation rates) in the oligotrophic waters of the North Pacific Ocean. All N substrates tested significantly stimulated phytoplankton growth and productivity. Urea resulted in the greatest (>300%) increases in chlorophyll a ( μ g L −1 and ∼0.19 μ g L −1 in the control and urea addition, respectively) and productivity ( μ mol C L −1 d −1 and ∼1.4 μ mol C L −1 d −1 in the control and urea addition, respectively) at two experimental stations, largely due to increased abundances of Prochlorococcus (Cyanobacteria). Two abundant clades of Prochlorococcus , High Light I and II, demonstrated similar responses to urea, suggesting this substrate is likely an important N source for natural Prochlorococcus populations. In contrast, the heterotrophic community composition changed most in response to . Finally, the time and magnitude of response to N amendments varied with geographic location, likely due to differences in microbial community composition and their nutrient status. Our results provide support for the hypothesis that changes in N supply would likely favor specific populations of phytoplankton in different oceanic regions and thus, affect both biogeochemical cycles and ecological processes.

Time-varying signal analysis to detect high-altitude periodic breathing in climbers ascending to extreme altitude - A. Garde; B. F. Giraldo; R. Jané; T. D. Latshang; A. J. Turk; T. Hess; M. M. Bosch; D. Barthelmes; T. M. Merz; J. Pichler Hefti; O. D. Schoch; K. E. Bloch (Medical & Biological Engineering & Computing, 2015)

Rates of dinitrogen fixation and the abundance of diazotrophs in North American coastal waters between Cape Hatteras and Georges Bank - M. R. Mulholland; P. W. Bernhardt; J. L. Blanco-Garcia; A. Mannino; K. Hyde; E. Mondragon; K. Turk; P. H. Moisander; J. P. Zehr (Limnology and Oceanography, 2012)
We coupled dinitrogen (N 2 ) fixation rate estimates with molecular biological methods to determine the activity and abundance of diazotrophs in coastal waters along the temperate North American Mid‐Atlantic continental shelf during multiple seasons and cruises. Volumetric rates of N 2 fixation were as high as 49.8 nmol N L −1 d −1 and areal rates as high as 837.9 µmol N m −2 d −1 in our study area. Our results suggest that N 2 fixation occurs at high rates in coastal shelf waters that were previously thought to be unimportant sites of N 2 fixation and so were excluded from calculations of pelagic marine N 2 fixation. Unicellular N 2 ‐fixing group A cyanobacteria were the most abundant diazotrophs in the Atlantic coastal waters and their abundance was comparable to, or higher than, that measured in oceanic regimes where they were discovered. High rates of N 2 fixation and the high abundance of diazotrophs along the North American Mid‐Atlantic continental shelf highlight the need to revise marine N budgets to include coastal N 2 fixation. Integrating areal rates of N 2 fixation over the continental shelf area between Cape Hatteras and Nova Scotia, the estimated N 2 fixation in this temperate shelf system is about 0.02 Tmol N yr −1 , the amount previously calculated for the entire North Atlantic continental shelf. Additional studies should provide spatially, temporally, and seasonally resolved rate estimates from coastal systems to better constrain N inputs via N 2 fixation from the neritic zone.

Production of endothelial nitric oxide synthase (eNOS) over-expressing piglets - Y. H. Hao; H. Y. Yong; C. N. Murphy; D. Wax; M. Samuel; A. Rieke; L. Lai; Z. Liu; D. C. Durtschi; V. R. Welbern; E. M. Price; R. M. McAllister; et al. (Transgenic Research, 2006)

Continuous real time ex vivo epifluorescent video microscopy for the study of metastatic cancer cell interactions with microvascular endothelium - Olga V. Glinskii; Virginia H. Huxley; James R. Turk; Susan L. Deutscher; Thomas P. Quinn; Kenneth J. Pienta; Vladislav V. Glinsky (Clinical & Experimental Metastasis, 2003)

Dimethyl sulphide and methanethiol formation in microbial mats: potential pathways for biogenic signatures - Pieter T. Visscher; Laura K. Baumgartner; Daniel H. Buckley; Daniel R. Rogers; Mary E. Hogan; Christopher D. Raleigh; Kendra A. Turk; David J. Des Marais (Environmental Microbiology, 2003)
Summary Mechanisms of dimethyl sulphide (DMS) and methanethiol (MT) production and consumption were determined in moderately hypersaline mats, Guerrero Negro, Mexico. Biological pathways regulated the net flux of DMS and MT as revealed by increases in flux resulting from decreased salinity, increased temperature and the removal of oxygen. Dimethylsulphoniopropionate (DMSP) was not present in these microbial mats and DMS and MT are probably formed by the reaction of photosynthetically produced low‐molecular weight organic carbon and biogenic hydrogen sulphide derived from sulphate reduction. These observations provide an alternative to the notion that DMSP or S‐containing amino acids are the dominant precursors of DMS in intertidal sediment systems. The major sink for DMS in the microbial mats was biological consumption, whereas photochemical oxidation to dimethylsulphoxide was the major sink for DMS in the overlying water column. Diel flux measurements demonstrated that significantly more DMS is released from the system during the night than during the day. The major consumers of DMS in the presence of oxygen were monooxygenase‐utilizing bacteria, whereas under anoxic conditions, DMS was predominantly consumed by sulphate‐reducing bacteria and methanethiol was consumed by methanogenic bacteria. Aerobic and anaerobic consumption rates of DMS were nearly identical. Mass balance estimates suggest that the consumption in the water column is likely to be smaller than net the flux from the mats. Volatile organic sulphur compounds are thus indicators of high rates of carbon fixation and sulphate reduction in these laminated sediment ecosystems, and atmospheric sulphur can be generated as a biogenic signature of the microbial mat community.

Genetic identity and homozygosity in North-Adriatic populations of Posidonia oceanica: An ancient, post-glacial clone? - Maria Valeria Ruggiero; R. Turk; G. Procaccini (Conservation Genetics, 2002)

Study of some immunological parameters in workers occupationally exposed to benzene - A. Bogadi-Šare; M. Zavalić; I. Trošić; R. Turk; I. Kontošić; I. Jelčić (International Archives of Occupational and Environmental Health, 2000)

Qualitative color vision impairment in toluene-exposed workers - M. Zavali?; Z. Mandi?; R. Turk; A. Bogadi- ?are; D. Plavec; L. J. Skender (International Archives of Occupational and Environmental Health, 1998)

Effects of Fumonisin and Moniliformin from Culture Materials to Growing Swine - R. B. Harvey; L. F. Kubena; G. E. Rottinghaus; J. R. Turk; S. A. Buckley (Cereal Research Communications, 1997)